Kelimpahan Tumbuhan Paku (Pteridophyta) di Hutan Desa Tanglapui, Kecamatan Alor Timur, Kabupaten Alor - Mowata, Johanis; Hendrik, Arnold Christian; Daud, Yanti (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2020)
This study aims to determine the composition of species, diversity, and density of ferns in the Forest area of ​​Tanglapui Village, East Alor District, Alor Regency. To make observations and divide the study site into 4 stations, namely: stasium 1 east, stasium 2 south, stasium 3 north, and stasium 4 western parts, which contained nail plants (pteridophyta). At each station two observation plots were installed for sampling. Placement of the observation plot using purposive sampling by determining the starting point and installing a plot measuring 20 m long and 10 m wide. Every nail plant found at the study site was recorded. The data obtained is then processed to see the number of nail species found, the abundance of each fern, and the index of diversity of ferns using the Shannon-Wiener diversity formula. The results showed that 22 species of ferns were found, namely Diplazium esculentum, Cyathea contaminans, Lygodium venustum sw, Drynaria quercifolia, Platycerium bifurcatum, Microsorum punctatum, Equisetum debile, Pteris biaurita L, Pytirogramma calomelanos, Polypodium virginianum sp. cuneatum, Pteris cretica L, Davallia denticulate, Asplenium attenuatum, Psilotum nudum L, Marsilia polycarpa, Pteris vittata, Nephrolepis biserrata, Pyrrosia piloselloidesi L MG, Macrothelipteris torresiana. One of the ferns that dominates the tanglapui forest area is Cyathea contaminans with a total of 509 individuals with a density of 0.32 individuals / m2. The value of diversity in the lowland tanglapui forests is 0.77.